Pengaruh Persepsi pada Promo Harbolnas 12.12 Shopee terhadap Konsumsi Non-Esensial : (Survei pada Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Negeri Surabaya) - Ana Ifadah; Dian Ayu Larasati; Nuansa Bayu Segara; Dhimas Bagus Virgiawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The development of e-commerce and digital payment systems has influenced students’ consumption patterns, including non-essential consumption. Shopee’s National Online Shopping Day (Harbolnas) 12.12 promotion offers various incentives that may shape perceptions and encourage consumption behavior among students. This study aims to analyze the perceptions of students of the Faculty of Social and Political Sciences, State University of Surabaya, toward Shopee’s Harbolnas 12.12 promotion and examine its influence on non-essential consumption. The research employed a quantitative approach with an associative design. A total of 382 students were selected using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using descriptive statistics and simple linear regression. The findings reveal that students’ perceptions of Shopee’s Harbolnas 12.12 promotion are categorized as positive and have a significant influence on non-essential consumption. The more positive the students’ perceptions of the promotional offers, the greater their tendency to purchase goods beyond their primary needs. These findings indicate that digital promotional stimuli can influence students’ consumption behavior through perceptual processes and provide empirical support for the Stimulus-Organism-Response (S-O-R) theory in explaining the relationship between promotional stimuli and consumption behavior.